The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s13399-022-03304-4
|View full text |Cite
|
Sign up to set email alerts
|

Dye removal using novel adsorbents synthesized from plastic waste and eggshell: mechanism, isotherms, kinetics, thermodynamics, regeneration, and water matrices

Abstract: High-density polyethylene (HDPE) waste and chicken eggshell were used to synthesize three novel adsorbents, namely mesoporous graphene (MG), nano-eggshell modified graphene (nEMG), and nano-magnetic eggshell modified graphene (nM-EMG) for methyl red (MR) adsorption from simulated wastewater. The effects of adsorption conditions (pH, contact time, initial dye concentration, adsorbent dose, and temperature) were investigated. MG, nEMG, and nM-EMG were characterized using SEM, TEM, BET, EDX, XRD, and FTIR analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 66 publications
2
4
0
Order By: Relevance
“…Howbeit, the removal efficiency remained approximately the same with increasing the biochar dose from 150 mg/L to 200 mg/L. The biochar particles might agglomerate with increasing the biochar loading above 150 mg/L which could result in the decline of active area, thereby suppressing the expected higher removal at excessive biochar doses as reported by and Salama et al ( 2022) 37,38 . The same trend was observed for the generated intermediates, where the concentration of the generated by-products increased from 0.9 mg/L to 3.9 mg/L in the case of caprylic acid and from 0.…”
Section: Investigation Of the Prepared Biochar Performance For Removi...supporting
confidence: 51%
“…Howbeit, the removal efficiency remained approximately the same with increasing the biochar dose from 150 mg/L to 200 mg/L. The biochar particles might agglomerate with increasing the biochar loading above 150 mg/L which could result in the decline of active area, thereby suppressing the expected higher removal at excessive biochar doses as reported by and Salama et al ( 2022) 37,38 . The same trend was observed for the generated intermediates, where the concentration of the generated by-products increased from 0.9 mg/L to 3.9 mg/L in the case of caprylic acid and from 0.…”
Section: Investigation Of the Prepared Biochar Performance For Removi...supporting
confidence: 51%
“…It has been reported that the increasing concentration of the dye boosts the mass transfer driving force via several collisions between dye molecules and the surface of the adsorbent at the initial stages of the adsorption process. 44 On the other hand, by increasing the MR concentration from 10 to 200 mg L À1 , the removal percentages of the NiO@HT-derived C composite and HT-derived C declined from 94.64 to 67.70%, and 90.78 to 57.21%, respectively (Table S1, ESI †). This is mainly attributed to the rising repulsion forces between the MR molecules on the surface of the adsorbent and the bulk phase after the initial adsorption.…”
Section: Materials Advances Papermentioning
confidence: 99%
“…This is mainly attributed to the rising repulsion forces between the MR molecules on the surface of the adsorbent and the bulk phase after the initial adsorption. 44,45 Overall, the adsorption capacity of the NiO@HT-derived C composite is much higher than that of the HT-derived C composite, which is mainly due to the higher surface area and porous structures. 46,47 3.2.2.…”
Section: Materials Advances Papermentioning
confidence: 99%
“…have been removed using adsorbent materials derived from plastic wastes such as cup-stacked CNTs, porous carbon materials, graphene-based materials, carbon nanofibers, etc. [109][110][111].…”
Section: The Use Of Other Adsorbents In Pollutant Removalmentioning
confidence: 99%